Genetic Improvement of Teak - Kumar, Vinod; Kotrange, H. R.; Dhotekar, U. P. (Indian Forester, 1998)
Genetic improvement of Teak has been undertaken under Maharashtra Van Sanshodhan Sanstha, Chandrapur in a systematic manner conducting identification of seed production areas, selection of plus trees, establishment of clonal Teak Seed Orchards and Teak Seedling Seed Orchards, establishment of Teak Germ Plasm Bank, as well as Bud Multiplication Gardens, Progeny testing and provenance trial. Thus efforts are being taken to produce genetically superior Teak trees by making use of principles of plant breeding. The works going on in MVSS, Chandrapur will go a long way in the field of Genetic Improvement of Teak.